2018
DOI: 10.3892/etm.2018.6062
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑124‑3p inhibits the progression of congenital hypothyroidism via targeting programmed cell death protein 6

Abstract: Abstract. The incidence of congenital hypothyroidism (CH) in newborn infants ranges from 1 in 3,000 to 1 in 4,000. Previous studies have indicated the neuroprotective role of microRNA (miR)-124-3p, however the expression and role of miR-124-3p in CH remain unclear. Therefore, the present study was performed to investigate the role and precise molecular mechanism of miR-124-3p in CH. Propylthiouracil (50 mg/day) was injected into the stomach of pregnant rats from gestational day 15 until parturition in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In addition, TH deficiency can lead to hippocampal neuronal cell injury and cell apoptosis (33). miRNAs have been revealed to serve a critical role in diseases associated with the nervous system, including autoimmune neuroinflammation (34), Alzheimer's disease (35), Parkinson's disease (36) and CH (16). A previous study has reported that miR-124 can protect neurons from apoptosis in rat models of hypothyroidism (16).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, TH deficiency can lead to hippocampal neuronal cell injury and cell apoptosis (33). miRNAs have been revealed to serve a critical role in diseases associated with the nervous system, including autoimmune neuroinflammation (34), Alzheimer's disease (35), Parkinson's disease (36) and CH (16). A previous study has reported that miR-124 can protect neurons from apoptosis in rat models of hypothyroidism (16).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been revealed to serve a critical role in diseases associated with the nervous system, including autoimmune neuroinflammation (34), Alzheimer's disease (35), Parkinson's disease (36) and CH (16). A previous study has reported that miR-124 can protect neurons from apoptosis in rat models of hypothyroidism (16). In the case of miR-1236, it has been reported to induce cell apoptosis in bladder cancer cells by inhibiting p21 expression (37).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations